2014
DOI: 10.1136/jnnp-2013-306995
|View full text |Cite
|
Sign up to set email alerts
|

Altered body schema processing in frontotemporal dementia with C9ORF72 mutations

Abstract: BackgroundMutations in C9ORF72 are an important cause of frontotemporal dementia (FTD) and motor neuron disease. Accumulating evidence suggests that FTD associated with C9ORF72 mutations (C9ORF72-FTD) is distinguished clinically by early prominent neuropsychiatric features that might collectively reflect deranged body schema processing. However, the pathophysiology of C9ORF72-FTD has not been elucidated.MethodsWe undertook a detailed neurophysiological investigation of five patients with C9ORF72-FTD, in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
5
29
2
1
Order By: Relevance
“…55 Our findings corroborate their observations. In fact, their results provide a useful framework for interpreting our findings, in particular the candidate mechanism of self/non–self-regulation.…”
Section: Discussionsupporting
confidence: 91%
“…55 Our findings corroborate their observations. In fact, their results provide a useful framework for interpreting our findings, in particular the candidate mechanism of self/non–self-regulation.…”
Section: Discussionsupporting
confidence: 91%
“…The findings are exploratory however they do converge with the hypothesis of Downey and colleagues who showed that C9orf72 carriers have an altered body schema (Downey et al, 2014). These authors suggested that altered body schema deficits might contribute to the development of psychosis generation in C9orf72 carriers through alterations in thalamo-cortico-cerebellar networks.…”
Section: Discussionsupporting
confidence: 80%
“…As such, we have seen renewed interest in psychosis in the Frontotemporal dementia-Amyotrophic lateral sclerosis (FTD-ALS) continuum, with recent systematic reviews of the literature suggesting that the prevalence is approximately 10–25% (Hall and Finger, 2015, Shinagawa et al, 2013). Neuroimaging studies of the C9orf72 expansion in both FTD and ALS have highlighted an excess of subcortical atrophy in comparison to non-carriers, and have led researchers to postulate that perhaps subcortical structures play a role in the generation of psychotic symptoms in C9orf72 cases but up until now this theory has not been explored (Bede et al, 2013b, Downey et al, 2014, Mahoney et al, 2012). The largest body of evidence regarding psychosis and associated brain abnormalities comes from the literature in schizophrenia and related psychotic disorders, where abnormal changes in the volume, connectivity and function of the frontal and temporal cortices, thalamus and cerebellum have been reported (Andreasen et al, 1996, Byne et al, 2009, Fusar-Poli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another case is the one of hemiplegic patients that can feel ownership over another person performing an action, even when the arm is in the position of the limb over which they have no control (Garbarini et al, 2015). Moreover, some dementias (e.g., frontotemporal dementia) can also affect patient's sense of ownership (measured by the rubber hand illusion) and sense of agency (using a test for the attribution of an action) (Downey et al, 2014). Interestingly, Alzheimer's patients seem to have a similar self-perception than their healthy counterparts, but with defects in the attribution of self- vs. non-self memories (Bond et al, 2016).…”
Section: Embodiment and Variabilitymentioning
confidence: 99%
“…We have not found any reports on possible genetic factors altering the sense of embodiment in healthy individuals, but there are specific mutations in patients affected by frontotemporal dementia that correspond to self-perception alterations. For example, the presence of C9ORF72 or MAPT mutations correlate to different embodiment defects (Downey et al, 2014). In addition, we have previously mentioned that schizophrenic patients have an increased sense of agency (Garbarini et al, 2016) and several genetic factors have been associated to this condition using genome-wide association studies (GWAS) (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014; Sekar et al, 2016).…”
Section: Possible Embodiment-related Molecular Mechanismsmentioning
confidence: 99%